2019
DOI: 10.1097/pec.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intranasal Ketamine in Pediatric Patients in the Emergency Department

Abstract: Objectives: Ketamine is a safe and widely used sedative and analgesic in the pediatric emergency department (ED). The use of intranasal (IN) ketamine in exchange for the administration of intravenous sedatives or analgesics for procedural sedation in pediatric patients is not commonplace. The goal of this study was to evaluate provider perceptions and patient outcomes at varying doses of IN ketamine for anxiolysis, agitation, or analgesia.Methods: From January 2018 to May 2018, we performed a prospective surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The median (IQR) behavior score before administration was 1 (1-3), which correlates with "crying and resisting". It improved to a median (IQR) score 30 minutes after administration to 6 (3.5-7), which correlates with "drowsy, sleepy, and lethargic", and finally it recovered with a median (IQR) score of 4.5 (3)(4)(5), which is between "calm and cooperative" and "alert and awake". Dexmedetomidine Use for Anxiolysis in the ED and 2 minutes after receiving 0.46 mg/kg IV ketamine for procedural sedation, he experienced bradycardia with a lowest documented heart rate of 65 beats per minute and respiratory depression with lowest documented respiratory rate of 12 breaths per minute.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median (IQR) behavior score before administration was 1 (1-3), which correlates with "crying and resisting". It improved to a median (IQR) score 30 minutes after administration to 6 (3.5-7), which correlates with "drowsy, sleepy, and lethargic", and finally it recovered with a median (IQR) score of 4.5 (3)(4)(5), which is between "calm and cooperative" and "alert and awake". Dexmedetomidine Use for Anxiolysis in the ED and 2 minutes after receiving 0.46 mg/kg IV ketamine for procedural sedation, he experienced bradycardia with a lowest documented heart rate of 65 beats per minute and respiratory depression with lowest documented respiratory rate of 12 breaths per minute.…”
Section: Resultsmentioning
confidence: 99%
“…4 Ketamine can also be used for analgesia or anxiolysis in pediatric patients, and respiratory depression is relatively uncommon. 5 However, ketamine may cause nausea and vomiting, and at high doses may cause a dissociative reaction, adding to distress in an agitated patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study found that orally administered choral hydrate was safe, implementation of a non-invasive modality requires a relatively clear dose–response relationship, an agent with a short half-life, and fewer AEs such as vomiting. [27–31] Large-scale, prospective multicenter studies are needed to establish the safety and efficacy of oral chloral hydrate in pediatric patients undergoing sedation for diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggest that the usefulness of chloral hydrate for sedation is dependent on the treatment protocol. Although this study found that orally administered choral hydrate was safe, implementation of a noninvasive modality requires a relatively clear dose-response relationship, an agent with a short half-life, and fewer AEs such as vomiting [23][24][25][26][27]. Large-scale, prospective multi-center studies are needed to establish the safety and e cacy of oral chloral hydrate in pediatric patients undergoing sedation for diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%